2018
DOI: 10.22603/ssrr.2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background of degenerative disc disease in the lumbar spine

Abstract: Abstract:This is a review paper on the topic of genetic background of degenerative disc diseases in the lumbar spine. Lumbar disc diseases (LDDs), such as lumbar disc degeneration and lumbar disc herniation, are the main cause of low back pain. There are a lot of studies that tried to identify the causes of LDDs. The causes have been categorized into environmental factors and genetic factors. Recent studies revealed that LDDs are mainly caused by genetic factors. Numerous studies have been carried out using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 116 publications
0
27
0
2
Order By: Relevance
“…Further, recent genome‐wide association meta‐analyses identified novel candidate genes, including PARK2 and CHST3 . An excellent review focusing on the extensive candidate genes was published recently . Many of these candidate genes are known to constitute the extracellular matrix (ECM) of IVD or be involved in ECM turnover, and, thus, they determine the size and mechanical property of the IVD by nature.…”
Section: Risk Factors For Idd From Epidemiologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, recent genome‐wide association meta‐analyses identified novel candidate genes, including PARK2 and CHST3 . An excellent review focusing on the extensive candidate genes was published recently . Many of these candidate genes are known to constitute the extracellular matrix (ECM) of IVD or be involved in ECM turnover, and, thus, they determine the size and mechanical property of the IVD by nature.…”
Section: Risk Factors For Idd From Epidemiologic Studiesmentioning
confidence: 99%
“…33 An excellent review focusing on the extensive candidate genes was published recently. 34 Many of these candidate genes are known to constitute the extracellular matrix (ECM) of IVD or be involved in ECM turnover, and, thus, they determine the size and mechanical property of the IVD by nature. Genetic defects in these genes presumably render the IVD more vulnerable against external force, leading to early onset of IDD.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…It has been suggested that the factors mediating these changes are genetic, nutritional and mechanical (65,66). Several twin studies of disc degeneration exist, most of them conducted by Battié et al (67). The studies by Battié et al are based on the "Twin Spine Study" and in a review from 2009 they summarized their findings (66).…”
Section: Pathophysiologymentioning
confidence: 99%
“…A number of excellent reviews have been published focussing largely on the extensive candidate gene literature [ 25 •, 26 •]. The genetic variants and studies which will be discussed have been selected to highlight findings reported in the past 5 years with a particular focus on those found associated using agnostic methods.…”
Section: Structure and Function Of Intervertebral Discmentioning
confidence: 99%